PERKEMBANGAN KOSAKATA BAHASA INDONESIA - ROSTINA . (JURNAL ILMIAH MAKSITEK, 2022)
Vocabulary in a language will always experience development over time. Development is a process that has occurred naturally directed and scientific. Indonesian then developed due to contact with various speakers of other languages ​​either through trade, marriage or globalization. In the field of science and technology, foreign languages ​​are the main source and contribute to enriching Indonesian vocabulary. In addition, the influence of regional languages ​​in daily communication is also a development factor that is unavoidable both in terms of adding numbers and changing meanings. Regional languages ​​with a large number of speakers also make a large contribution to the development of Indonesian vocabulary. Vocabulary development is a condition of increasing, decreasing or changing the form and meaning of vocabulary in a language. The development of Indonesian vocabulary is needed to complete deficiencies in Indonesian. In order for the Indonesian language to continue to exist to fulfill its position and function, it is necessary to accelerate the development of vocabulary or terms in various fields of knowledge.